Landasan Pengembangan Kurikulum Merdeka - Yenti, Desmy; Hefrita, Nelly Octovia; Fadriati, Fadriati (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to describe the basis for the development of the independent curriculum. In this article, the analysis of research methods uses literature studies from various available sources. The method used is literature. This research is a type of research that collects data from literature. The data collection technique in this study is documentation, namely looking for written sources that contain information on the topics discussed. Primary data was obtained from reading reference books, journals, and websites. Based on the results of the research carried out, the foundations for the development of the independent curriculum are (1) the philosophical foundation, which is to discuss and identify the philosophical foundations and their application in developing the curriculum, (2) the psychological foundation, which is a study centered on understanding and studying human behavior, (3) the sociological foundation, which discusses and identifies the sociological, scientific and technological foundations, as well as their application in developing the independent curriculum,  (4) the foundation of technology, namely the optimal use of technology will have a positive impact on the development of the independent curriculum, (5) the historical foundation, the development of the independent curriculum refers to various historical experiences that affect the curriculum developed and (6) the philosophy of KHD, which is to carry out student-centered learning that is in accordance with learning in the independent curriculum. The advantages of the independent curriculum are simpler and more in-depth, more independent, more relevant, interactive, and communicative.